Arawan antisociologies: modes of relation in Western Amazonia - Aparicio, Miguel (Revista de Antropología Social, 2021)
The interfluvial zone between the basins of the Purus and Jurua rivers, in the Brazilian Western Amazonia, has been characterized by the low density of historical, archaeological and linguistic research. This area concentrates a circuit of indigenous peoples compounding the Arawan linguistic family which, for the last 15 years, have been the focus of attention for new ethnographies. This article develops a crossing between the analysis of recent anthropological investigations in the region and ethnographic fieldwork outcomes with two groups of the Arawan complex: Banawa and Suruwaha, with special focus on the processes of composition of collectives. Their forms of sociality manifest a kind of disregard with ethnic borders, with movements of resistance to social morphologies or stable sociological boundaries. The Arawan develop a chromaticism in their relationships that leads us to recognize in them an anti-sociology set up by relations in-between rather than by the constitution of solid ethnic groups.